Identifying the determinants of and barriers to landowner participation in reforestation in Costa Rica. (May 2019) - Powlen, Kathryn A.; Jones, Kelly W.
Highlights: Decisions to participate in reforestation programs are strongly influenced by pro-environmental motivations. External support from conservation organizations play a significant role in landowner's decision to plant trees. Contextual factors, including farm size and length of residency, influence the decision to plant trees. Lack of knowledge, unsuccessful past experiences, and upfront financial investments are barriers to planting trees. Abstract: Reforestation programs are being implemented across the globe to address the decline in global forest cover. This research examines the role of motivations, external support, and barriers on farmer participation in reforestation in the tropics. Eighty-five household surveys and 18 in-depth interviews were conducted with farmers and organizations in Costa Rica. To measure motivations, we asked farmers' their perceptions of environmental, social and financial outcomes of reforestation. External support was measured as perceived support from conservation organizations. Regression models were used to determine the significance of motivations and external support, controlling for household and biophysical characteristics, on reforestation behaviors. External support and environmental motivations both had a positive and statistically significant effect on reforestation. Farm size and the number of years spent on the property also positively influenced the decision to plant trees. Farmers identified instrumental pro-environmental values, such as water regulating ecosystem services, as their primary motivations for planting trees. Barriers to reforestation included a lack of technical skills for planting trees, unsuccessful past experiences, a lack of trust in external organizations and initial reforestation costs. Overall, this research indicates that environmental motivations influence the decision to participate in reforestation, but that external support is critical for overcoming initial participation barriers.